Rate of water loss and sugar uptake during the osmotic dehydration of pineapple - Ramallo, Laura Ana (2005)
Water loss, sucrose gain and the variation in concentration of other natural fruit sugars (glucose and fructose) were studied during osmotic dehydration of pineapple slices (0.6 mm thick) in sucrose solution (60 % w/w) at three temperatures (30, 40 and 50°C). As temperature increased from 30 to 50°C, the apparent moisture and sucrose diffusivities (Dw and Ds) increased 3.8 and 2.8 times, respectively, therefore, the dehydration efficiency index (Dw/Ds) increased with temperature. The loss of glucose and fructose increased with temperature too. It was found that the solute content was a linear function of the moisture content and this relation was independent of the temperature during the first 600 minutes of dehydration.